The Effect of Argumentation-Supported Problem-Based Learning Method in Teaching Chemical Equilibrium and Le-Chatelier’s Principle - Hatice Güngör Seyhan; Gülseda Eyceyurt Türk (Mimbar Sekolah Dasar, 2022)
This study aims to examine the effects of argumentation-supported problem-based learning (AS-PBL) carried out in the Chemistry-II laboratory course on the conceptual understanding of prospective science teachers about "Chemical equilibrium and Le-Chatelier's principle". The prospective teachers' answers were analyzed using content analysis and the existing misconceptions about the relevant chemistry topics were determined and the effectiveness of the relevant method in eliminating the misconceptions was also examined. The prospective science teachers had fewer scientific arguments in writing grounds for their claims before the treatment using AS-PBL. They were able to use their rebuttal skills more in addition to their claims and grounds after the treatment. Suggestions about problem-based learning supported by argumentation in science laboratory environments were presented to prospective teachers, educators and, readers.